Effects of the brown rice diet on visceral obesity and endothelial function: the BRAVO study. Issue 2 (28th January 2014) - Shimabukuro, Michio; Higa, Moritake; Kinjo, Rie; Yamakawa, Ken; Tanaka, Hideaki; Kozuka, Chisayo; Yabiku, Kouichi; Taira, Shin-Ichiro; Sata, Masataka; Masuzaki, Hiroaki
<x content-type="archive" xml:space="preserve">Abstract</x> Brown rice (BR) and white rice (WR) produce different glycaemic responses and their consumption may affect the dietary management of obesity. In the present study, the effects of BR and WR on abdominal fat distribution, metabolic parameters and endothelial function were evaluated in subjects with the metabolic syndrome in a randomised cross-over fashion. In study 1, acute postprandial metabolic parameters and flow- and nitroglycerine-mediated dilation (FMD and NMD) of the brachial artery were determined in male volunteers with or without the metabolic syndrome after ingestion of either BR or WR. The increases in glucose and insulin AUC were lower after ingestion of BR than after ingestion of WR (P= 0·041 and P= 0·045, respectively). FMD values were decreased 60 min after ingestion of WR (P= 0·037 v. baseline), but the decrease was protected after ingestion of BR. In study 2, a separate cohort of male volunteers (n 27) with the metabolic syndrome was randomised into two groups with different BR and WR consumption patterns. The values of weight-based parameters were decreased after consumption of BR for 8 weeks, but returned to baseline values after a WR consumption period. Insulin resistance and total cholesterol and LDL-cholesterol levels were reduced after consumption of BR. In conclusion, consumption of BR may be beneficial, partly owing to the lowering of glycaemic response, and may protect postprandial endothelial function in subjects with the metabolic syndrome. Long-term beneficial effects of BR on metabolic parameters and endothelial function were also observed.